CIRCULAR ARTIFICIAL DIELECTRIC MATERIAL OF ANISOTROPIC PERMITTIVITY AND ITS APPLICATION ON MICROSTRIP ANTENNA - - NIM:33212015 , HepiLudiyati
The usage of natural dielectric materials in telecommunication devices have began todecrease,especiallysinceresearchersintheﬁeldofelectromagneticproposedthe artiﬁcial dielectric materials with many unique characteristics. Natural dielectric materials which are produced by factories through the chemical processes have permittivity with limited value variations. This condition resulted difﬁculties in improving the performance of telecommunication devices. Unlike the natural dielectric material, the artiﬁcial dielectric material is made from the electromagnetismprocess,bymodifyingtheelectromagneticpropertiesofthenaturaldielectric material. These properties are expressed by a parameter called permittivity. By using this process, the permittivity of the material can be increased or converted into a new permittivity value which canÃ‚Â’t be found in natural dielectric material, one of which is the anisotropic permittivity. The characteristic of anisotropic permittivity which is a tensor permittivity, has been explored by the researchers, whom are generally from Japan. One of the explorations are anisotropic permittivity capabilities in the miniaturization of the telecommunicationdeviceÃ‚Â’ssize. MiniaturizationofthetelecommunicationdeviceÃ‚Â’s size is needed especially for telecommunication devices which work on VHF frequencies and some frequencies on lower UHF frequencies. Technically, the miniaturizationsizeofthetelecommunicationdevicessuchasantenna,ﬁlter,power divider, and resonator require the use of high-permittivity dielectric materials. The literatures on miniaturization size of the telecommunication devices have proposed a method of increasing the permittivity value only by the x-, y- or z-direction. Within this case the anisotropic properties are described in a Cartesian coordinate system. The increased method of the permittivity value was done by adding small squareshaped conductor layers throughout the process of etching. These conductor layers were added on top of the natural dielectric material layer termed as host material. In this method, host material could be used only in the form of a printed circuit board or PCB. By setting the size, number, orientation and the density of the conductor layers as well as the distance between the conductor layers had effectively increased the permittivity value in a particular direction that affects the iv miniaturization of the size of the bandpass ﬁlter which is working on the TE01δ mode. Unfortunately,theexplorationoftheanisotropicpropertiesofmaterialswere only conducted by the Cartesian coordinate system and since 2006 the research on anisotropic dielectric material has not been developed yet. This dissertation develops a research on artiﬁcial dielectric material with an anisotropic permittivity in a cylindrical coordinate system. The anisotropic permittivity is set within the ρ-direction, φ-direction, and z-direction. This dissertation explores the anisotropic permittivity capability in miniaturization of telecommunication deviceÃ‚Â’s size which has a circular physical construction. The exploration is done through theoretical, numerical and experimental studies. In theoretical and numerical studies, an artiﬁcial dielectric material with anisotropic permittivity is encapsulated in a circular cavity resonator. The resonator is termed asanartiﬁcialcavityresonator. Theresonantfrequenciesgeneratedbytheartiﬁcial cavity resonator have been characterized in TE and TM modes. The resonance frequency as a function of material thickness and anisotropic permittivity value has beenformulatedbyvariableseparationmethodandshortopenterminationmethod by considering the electrical ﬁeld boundary conditions on the conductor walls of the circular cavity resonator. ThepotentialminiaturizationofthetelecommunicationdeviceÃ‚Â’ssizehasbeeninvestigated by comparing the resonant frequency which is generated by the artiﬁcial cavity resonator with the resonant frequency of a conventional cavity resonator. The conventionalcavity resonatoris amention of acircular cavityresonator which it is encapsulated by the natural dielectric material. In a numerical study, the resonant frequencies generated by the artiﬁcial and conventional cavity resonators have been calculated using the FDTD method. The FDTD method is constructed by the Maxwell equations of 3 dimensions in differential forms. The solution of the FDTD method is the time domain of electric and the magnetic ﬁelds amplitude that present in the artiﬁcial cavity resonator. Using FFT process, the resonant frequencythatgeneratedbytheartiﬁcialcavityresonatorcanbedetermined. From these studies, the results have shown that the resonant frequencies generated by the artiﬁcial cavity resonator are lower than the resonant frequencies generated by the conventional cavity resonator. In TE mode, anisotropic permittivity in the ρ-direction has resulted the highest percentage of resonance frequency lowering, especially in the dominant mode, i.e. TE11δ mode. The percentages generated from the theoretical and numerical studies are 13.77 % and 14.2 %, respectively. InTMmode,anisotropicpermittivityinthez-directionhaseffectivelydecreasedthe resonant frequency even if the percentage is higher than the TE mode percentage. In the dominant mode, which is the TM01 delta mode, the resonant frequencies generated through theoretical and numerical studies are 43.07 % and 42.52 %, respectively. While the other TM modes are 35.98 % and 37.95 % for TM11δ and 34,86 % and 36.35 % for mode TM21δ. From the results of theoretical and numerical studies, there are the potentials for selecting TE or TM wave modes on dielectric materials with anisotropic permittivity. Furthermore, the potential of anisotropic permittivity in miniaturization of telecommunication deviceÃ‚Â’s sizes was v implemented on microstrip antenna devices. Microstrip antenna is designed and fabricated at VHF and UHF frequencies. The experiment within this dissertation is anisotropic permittivity in the z-direction. To generate anisotropic permittivity in the z-direction, the amount of 0.5 mm diameter conductor wires are implanted perpen-dicularly through the surface of host material. To increase the permittivity value in the z-direction, the wires are implanted in the position of the maximum electric ﬁeld from the TM11 mode electric ﬁeld distribution. Thehostmaterialthatisusedisadielectricmaterialwhichisavailableeasilyonthe market with a low cost, i.e. styrofoam, acrylic, ﬂoral foam, and FR-4 epoxy. The return loss of artiﬁcial microstrip antenna which is called for microstrip antenna is fabricated using the artiﬁcial dielectric material which has been measured and compared with return loss of conventional microstrip antenna. The conventional microstrip antenna which is a mention for a microstrip antenna that fabricated usinganaturaldielectricmaterial. Themeasurementhasbeenconductedbysetting dimension of both radiator microstrip antennas equally. From the measurement result, it result shows that the working frequencies of the artiﬁcial microstrip antenna on the four host material are lower than the working frequencies of the conventional microstrip antenna. The working frequencies are the frequencies in whichthereturn loss valueisboundednotless than10dB.Thebest result isshown when110conductorwiresareplacedthroughthesurfaceofstyrofoam. Thecentral frequency of the artiﬁcial microstrip antenna is lower than the frequency of the conventional microstrip antenna from 1832.3 MHz down to 1095.7 MHz. The results of theoretical, numerical and experimental studies have shown that the artiﬁcialdielectricmaterialwithanisotropicpermittivityinacylindricalcoordinate systems has a good potential in the miniaturization of the telecommunication deviceÃ‚Â’ssize. Thepotentialhasbeendemonstratedbythelowresonantfrequencyin acircularcavityresonatorandthelowworkingfrequencyofthemicrostripantenna. The planting of conductor wires in the position of the maximum electric ﬁeld of TE or TM modes can provide ﬂexibility in setting the permittivity value of dielectric material. The permittivity setting capability can be taken into consideration by an engineer in the selection of an inexpensive artiﬁcial dielectric material type when miniaturizing the size of telecommunication devices as well as for the purpose of improving the performance of telecommunication equipment.